Queer religiosities: an introduction to queer and transgender studies in religion - Wilcox, Melissa M. (Rowman & Littlefield, 2021)
"Queer Religiosities is a comprehensive, comparative, globally-focused textbook that introduces students to queer studies in religion. It is organized in a comparative, thematic format that allows readers to approach the study of queer religion from a variety of angles while teaching key principles in the study of religion and the study of sexuality and gender. Queer Religiosities aims to make the rapidly growing research in queer studies in religion accessible to students"--